2020
DOI: 10.5045/br.2020.2020219
|View full text |Cite
|
Sign up to set email alerts
|

Utility of screening tools to differentiate beta thalassemia trait and iron-deficiency anemia - do they serve a purpose in blood donors?

Abstract: Background The aim of this study was to estimate the prevalence of the beta thalassemia trait (BTT) and differentiate it from iron-deficiency anemia (IDA) among blood donors. Methods A total of 1,000 samples from blood donors were subjected to complete hemogram with red blood cell indices. Further, Mentzer index (MI) was calculated for samples with mean corpuscular volume (MCV) below 80 fL and mean corpuscular hemoglobin (MCH) below 27 pg. Samples with Mentzer index <12 were subjected to naked-eye single-tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
(39 reference statements)
1
3
0
1
Order By: Relevance
“…Progressive iron overload affects multiple organs and is the leading cause of death in patients with β-thalassemia major [17]. Consistent with other studies in the literature, in our study, the serum iron level of the patient group was found to be statistically signi cantly higher than the control group [10,[18][19][20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Progressive iron overload affects multiple organs and is the leading cause of death in patients with β-thalassemia major [17]. Consistent with other studies in the literature, in our study, the serum iron level of the patient group was found to be statistically signi cantly higher than the control group [10,[18][19][20].…”
Section: Discussionsupporting
confidence: 90%
“…In beta thalassemia major disease, ineffective erythropoiesis and hemolytic anemia occur as a result of imbalance in globin chain ratio and precipitation of unpaired chains [10,11]. In thalassemia major, RBC indices show hypochromic microcytic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…21 Alam et al also found more or less similar results. 18 When compared with other hematological indices used to differentiate between the two important causes of microcytic hypochromic anemia, Mentzer index has proved to be most reliable in a study conducted by Vehapoglu A et al 22 Similar results were also documented by Sundh A et al 23 In brief, important differential diagnoses of microcytic hypochromic anemia are iron deficiency anemia and beta thalassemia. Both of these necessitate specific tests for confirmation which are not only expensive but also not easily available.…”
Section: Discussionmentioning
confidence: 61%
“…In a small study in Malaysia, 13 out of 80 blood donors had a type of minor β-thalassemia [ 40 ]. Thalassemia screening of blood donors could have another benefit—informing donors of their trait status could help prevent the birth of babies with severe hemoglobinopathies [ 40 , 41 , 42 ]. Microcytic RBCs have been named as a production challenge for platelet and plasma production as well [ 40 ].…”
Section: Red Blood Cellsmentioning
confidence: 99%